A Case of Aplastic Anemia Associated With Long-Term Metronidazole Use. (August 2020) - Sam, Andrew M.; Saunders, Ila M.; Taplitz, Randy; Koura, Divya
Metronidazole is a nitroimidazole antibacterial agent that is highly effective for the treatment of protozoal and anaerobic infections. Metronidazole is known to cause hematologic adverse effects, including a reversible mild neutropenia; in rare circumstances, thrombocytopenia has been associated with metronidazole treatment. We present a case of aplastic anemia related to the extended use of metronidazole.